Role of the gene Phlda1 in fenvalerate-induced apoptosis and testicular damage in Sprague-Dawley rats. Issue 15 (3rd August 2019) - Hong, Ting; Li, Ru; Sun, Lu-Lu; Xu, Jie; He, Meng-Ting; Wang, Wei; Yan, Rui; Tong, Jian; Zhang, Jie
ABSTRACT: Fenvalerate (FEN), a pyrethroid insecticide used worldwide, has been shown to produce a potentially adverse effect on male reproduction. However the mechanisms are not completely understood. Thus this study aimed to (1) determine whether cellular apoptosis was involved in FEN-induced testicular damage in rats, and (2) identify the potential mechanism involved in FEN-induced apoptosis in testes. Data demonstrated that FEN markedly decreased serum testosterone levels, increased the inner diameter of seminiferous tubules, decreased the layers of spermatogenic cells, disturbed spermatogenesis and increased the number of apoptotic cells. Further, bioinformatic analysis of gene microarray in rat testis tissue showed that FEN significantly altered the expressions of genes ( Krt8, Mal, Cd24, Lcn2, Phlda1, Arg2 ) related to apoptotic related processes. The expression pattern of these 6 genes was upregulated in FEN-treated rat testicular tissue. qRT-PCR analysis demonstrated that Phlda1, a well-documented pro-apoptotic factor, was significantly elevated by FEN. The expression of PHLDA1 testicular protein was also elevated following FEN exposure. In conclusion, our results suggest that FEN exposure induced deleterious effects on rat testes associated with Phlda1 -mediated apoptosis which may act as a molecular mechanism underlying FEN induced rat testicular damage.